Polysaccharide Based Supercapacitors - Yee Liew, Soon; Thielemans, Wim; Freunberger, Stefan; Spirk, Stefan (Springer International Publishing : Imprint: Springer, 2017)
This book provides an excellent introduction into polysaccharide-based supercapacitors. It includes fundamental knowledge on supercaps as well as an overview of currently available approaches reported in the literature. Written by an international team of leading academics, this brief is aimed at a variety of readers with an interest in polysaccharide science and its applications.
Keywords: Chemistry.; Energy storage.; Electrochemistry.; Surfaces (Physics).; Interfaces (Physical sciences).; Thin films.; elektronické knihy; electronic books